Gaya Kepemimpinan dalam Manajemen Keuangan Pesantren - Nafia, Ilman; Ulfah, Mariyah (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study examines leadership styles in financial management at the Attarbiyatul Wathoniyah Islamic Boarding School (PATWA) Mertapada, Cirebon Regency. The main focus is how the leadership style of the boarding school leaders influences the financial management of the boarding school which includes budget planning, transaction recording, and business unit management. The method used is a case study with data collection through interviews, observations, and documentation. The results of the study indicate that transformational leadership style combined with charismatic leadership is the key to success in creating emotional involvement and high commitment of administrators in managing finances in a trustworthy and responsible manner. This leadership builds an organizational culture that upholds the values ​​of sincerity, responsibility, and transparency, although the financial recording system is still manual and minimally digitized. Elements of transactional leadership are also present through the provision of incentives to business unit administrators who succeed in achieving targets, which increases motivation and efficiency. However, high dependence on the main leadership figure is a challenge for the sustainability of the boarding school's financial management. Therefore, strengthening the documentation system and leadership cadreship are important recommendations so that the boarding school's financial management can run professionally and sustainably.